LARD: a new lymphoid-specific death domain containing receptor regulated by alternative pre-mRNA splicing. - Screaton, G; Xu, X; Olsen, A; Cowper, A; Tan, R; McMichael, A; Bell, J (1997)
Fas and TNF-R1 are cysteine-rich cell surface receptors related to the low-affinity nerve growth factor receptor family. Engagement of these receptors by their respective ligands, FasL and tumor necrosis factor, leads to apoptosis that is signaled through a conserved intracellular portion of the receptor termed the "death domain." We have cloned a new member of this family, lymphocyte-associated receptor of death (LARD), which leads to spontaneous apoptosis when expressed in 293T cells. The expression of LARD is more tightly regulated than that of either Fas or TNF-R1 as it is found predominantly on lymphocytes (T and B cells) but not on macrophages or a number of transformed lymphocyte cell lines. Alternative pre-mRNA splicing generates at least 11 distinct isoforms of LARD. The full-length isoform, LARD-1, extends to include the transmembrane and death domains, whereas the other isoforms encode potentially secreted molecules. Naive B and T cells express very little LARD-1 but express combinations of the other isoforms. Upon T cell activation, a programmed change in alternative splicing occurs so that the full-length, membrane-bound LARD-1 predominates. This may have implications for the control of lymphocyte proliferation following activation.